2021
DOI: 10.3390/ijgi10020063
|View full text |Cite
|
Sign up to set email alerts
|

A GIS-Based System for Spatial-Temporal Availability Evaluation of the Open Spaces Used as Emergency Shelters: The Case of Victoria, British Columbia, Canada

Abstract: Canadian emergency management planners have historically ignored the self-motivated evacuation procedures of people who cannot initially choose the safest evacuation areas. In densely developed urban areas, open spaces can be seen as ideal evacuation areas and should thus be included in shelter planning. In this study, the public open spaces in Great Victoria were selected as the study area and evaluated using GIS technologies. A multi-criteria TOPSIS evaluation model was used to conduct comprehensive quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…Moreover, it is also possible to use the overall OS length to compare different urban areas, using the street network density index, defined as the ratio between the total length of streets within a sector and the sector's overall area [55]. Lastly, the OS's area has a particular role in estimating the ability of ASs (e.g., squares, parking) to be used as secure spaces [29,61]. The "temporary secure OSs" index expresses the ratio between the total area of secure OSs and the number of evacuees [12].…”
Section: Morpho-typological Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it is also possible to use the overall OS length to compare different urban areas, using the street network density index, defined as the ratio between the total length of streets within a sector and the sector's overall area [55]. Lastly, the OS's area has a particular role in estimating the ability of ASs (e.g., squares, parking) to be used as secure spaces [29,61]. The "temporary secure OSs" index expresses the ratio between the total area of secure OSs and the number of evacuees [12].…”
Section: Morpho-typological Characteristicsmentioning
confidence: 99%
“…The accessibility for vehicles/pedestrians describes the exclusive use or not of the OS, which notably affects the type and speed of evacuation flow after a disastrous event [42,59] or the possibility of being reached by emergency services [61]. Different types of flows along the same LS during the evacuation phase have an impact on the risk for pedestrians, especially considering the different mental state of the drivers compared to ordinary days [57,62] or the possibility of having multi-directional movements in the same OS, especially in the ASs [29].…”
Section: Characteristics Of Use and Usersmentioning
confidence: 99%
See 2 more Smart Citations
“…Su et al [14] developed a two-stage floating catchment (2SFCA) method with variable service radius, and evacuation radius has been developed to describe emergency shelter access in the main Lanzhou area and compare it with traditional 2SFCA. Yao et al [15] used a multicriteria TOPSIS evaluation model and, through a combined process, service area, and POI analysis, developed a model that provided an overall assessment at the district level. e results showed that the distribution of open spaces did not match the dynamics of population distribution.…”
Section: Introductionmentioning
confidence: 99%